2022
DOI: 10.1021/acs.orglett.2c02910
|View full text |Cite
|
Sign up to set email alerts
|

Total Synthesis of the Phenolic Steroid Myrmenaphthol A

Abstract: Myrmenaphthol A is a structurally unique phenolic steroid with a naphthyl AB-ring system and an unusual C2 hydroxy group. Herein, we report the first total synthesis of this natural product in 10 steps from inexpensive, commercially available sitolactone. Key features of the synthesis include a Baran decarboxylative coupling and a Friedel–Crafts cyclization/olefin isomerization/aromatization cascade that rapidly assembled the tetracyclic core framework. This synthetic strategy is expected to be readily amenabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 44 publications
(34 reference statements)
0
11
0
Order By: Relevance
“…Our retrosynthetic analysis, outlined in Scheme , was guided largely by Jung’s biosynthetic proposal for the formation of the TPR, as well as by our interest in utilizing sitolactone ( 20 ) as a chiral pool starting material for the construction of 6/5-fused ring systems . To maximize the synthetic efficiency, we sought to build the pentacyclic core framework by means of a convergent fragment-coupling approach .…”
Section: Resultsmentioning
confidence: 99%
“…Our retrosynthetic analysis, outlined in Scheme , was guided largely by Jung’s biosynthetic proposal for the formation of the TPR, as well as by our interest in utilizing sitolactone ( 20 ) as a chiral pool starting material for the construction of 6/5-fused ring systems . To maximize the synthetic efficiency, we sought to build the pentacyclic core framework by means of a convergent fragment-coupling approach .…”
Section: Resultsmentioning
confidence: 99%
“…[15] Previously, our group reported two examples for substrates of ene-yne-aldehydes leading to [6,7,5]-tricyclic compounds. [16] Furthermore, by small variation of enyne part this protocol was also extended towards the total synthesis of Taxamairin B and Rosmardiophenol as a [6,7,6] tricyclic core via gold catalyzed cyclization. However, the number of carbon chains was increased to give 1,7-enynals in the place of previously reported 1,6-enynals.…”
Section: Introductionmentioning
confidence: 99%
“…According to the mechanistic study of our group previously reported work the number of rings can be adjusted by increasing the carbon chain of the enyne-al unit (Figure 3). [17] However, to need [6,6,6] tricyclic compounds via [4 + 2] cycloaddition reaction, recently we studied the cyclization of 2-alkynylphenylcarbonyls (3) with a pendant double bond under gold and copper catalyst. In this study with failure to get [6,6,6]-tricyclic compound through gold catalyzed reaction by varying temperature and solvent, we found Cu(OTf) 2 as a best catalyst to underwent [4 + 2] cycloaddition via intermediate B (Figure 3).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In summary, we have achieved the first and asymmetric total synthesis of twin bufogargarizins A and B in 28 and 30 steps, respectively, from commercially available sitolactone . Remarkably, the synthetically challenging [7–5–6–5] tetracyclic core of bufogargarizin A was made efficiently by a unique intramolecular Ru-catalyzed [5 + 2] cycloaddition reaction.…”
mentioning
confidence: 99%